Childhood and adult tuberculosis in a rural hospital in Southeast Ethiopia: a ten-year retrospective study - Ramos Jose; Reyes Francisco; Tesfamariam Abraham (BMC, 2010)
Abstract Background Many DOTS experiences in developing countries have been reported. However, experience in a rural hospital and information on the differences between children and adults are limited. We described the epidemiology and treatment outcome of adult and childhood tuberculosis (TB) cases, and identified risk factors associated with defaulting and dying during TB treatment in a rural hospital over a 10-year period (1998 to 2007). Methods Retrospective data collection using TB registers and treatment cards in a rural private mission hospital. Information was collected on number of cases, type of TB and treatment outcomes using standardised definitions. Results 2225 patients were registered, 46.3% of whom were children. A total of 646 patients had smear-positive pulmonary TB (PTB), [132 (20.4%) children]; 816 had smear-negative PTB [556 (68.2%) children], and 763 extra-PTB (EPTB) [341 (44.8%) children]. The percentage of treatment defaulters was higher in paediatric (13.9%) than in adult patients (9.3%) (p = 0.001). The default rate declined from 16.8% to 3.5%, and was independently positively associated with TB meningitis (AOR: 2.8; 95% CI: 1.2-6.6) and negatively associated with smear-positive PTB (AOR: 0.6; 95% CI: 0.4-0.8). The mortality rate was 5.3% and the greatest mortality was associated with adult TB (AOR: 1.7; 95% CI: 1.1-2.5), TB meningitis (AOR: 3.6; 95% CI:1.2-10.9), and HIV infection (AOR: 4.3; 95% CI: 1.9-9.4). Decreased mortality was associated with TB lymphadenitis (AOR: 0.24; 95% CI: 0.11-0.57). Conclusion (1) The registration of TB cases can be useful to understand the epidemiology of TB in local health facilities. (2) The defaulter and mortality rate of childhood TB is different to that of adult TB. (3) The rate of defaulting from treatment has declined over time.